2015
DOI: 10.1103/physreve.91.013003
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion force in fluids: Effects of fingering, wetting, and viscous normal stresses

Abstract: Probe-tack measurements evaluate the adhesion strength of viscous fluids confined between parallel plates. This is done by recording the adhesion force that is required to lift the upper plate, while the lower plate is kept at rest. During the lifting process, it is known that the interface separating the confined fluids is deformed, causing the emergence of intricate interfacial fingering structures. Existing meticulous experiments and intensive numerical simulations indicate that fingering formation affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In many practical applications, the emergence of these hydrodynamic instabilities is undesirable and because of that much attention has been devoted to devising strategies for controlling the growth of such patterns. However, all existing studies that somehow try to control the emergence of these interfacial disturbances neglect the effects of the wetting film left behind by the displaced fluid during the flow, even though a considerable number of works [20,[39][40][41][42][43][44][45][46][47][48][49][50] have pointed to the fact that wetting has an important role in the nonlinear finger formation process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many practical applications, the emergence of these hydrodynamic instabilities is undesirable and because of that much attention has been devoted to devising strategies for controlling the growth of such patterns. However, all existing studies that somehow try to control the emergence of these interfacial disturbances neglect the effects of the wetting film left behind by the displaced fluid during the flow, even though a considerable number of works [20,[39][40][41][42][43][44][45][46][47][48][49][50] have pointed to the fact that wetting has an important role in the nonlinear finger formation process.…”
Section: Discussionmentioning
confidence: 99%
“…A number of subsequent theoretical and experimental investigations in rectangular Hele-Shaw cells [40][41][42][43][44] have indicated that the inclusion of wetting effects helps to provide a better match between theory and experiments. This has also been the case for injection-driven flows in the radial Hele-Shaw cell setup [45][46][47][48][49] and for time-dependent gap flows in the lifting Hele-Shaw arrangement [20,50]. In particular, by employing a weakly nonlinear analysis, the authors of Ref.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The contribution of hydrodynamic forces to adhesion has mostly been investigated for standard configurations such as plate-plate or ball-plate in probe tack and colloid adhesion tests [20,23]. More complex geometries are of great interest for various applications and exist in natural wet adhesive systems, which are mainly composed of soft, deformable materials and non-regular geometries [12,[24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Nagel and Gallaire [13] used the Brinkman equation and took into account both normal and tangential viscous stresses to derive a quite complicated linear dispersion relation for the Saffman-Taylor instability, finding a good accordance with experiments. The consideration of interfacial fingering and normal viscous stresses effects has also been instrumental to provide a better agreement between theoretical predictions and experiments for fluid adhesion problems in Hele-Shaw geometry [14].…”
Section: Introductionmentioning
confidence: 99%